Study on Internet of Things Based Marine Entrepreneurship Development to Increase Women Income - Lestari, Soraya; Payana, Mahendar Dwi; Lisnawati, Lisnawati (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
The development of the marine sector processing industry continues to increase. Unfortunately, the increase is not evenly distributed at the MSME business level, especially since it is not yet fully able to adopt the technology. Currently, technology is like a bridge to generate income. The quality of dried Kemamah fish sold by women entrepreneurs on the coast is still not optimal and traditional. This study examines the readiness of women entrepreneurs in the marine sector to implement the IoT concept. The study was conducted by interviewing and collecting the necessary data and conducting a risk analysis based on the business model, making recommendations for IoT development to see the feasibility and quality of dried fish. This study was conducted using a descriptive analysis method with a qualitative approach. The study results show that the use of IoT affects women's income, where product quality, product selling value, efficiency, human resources, and the application of IoT-based technology can indirectly affect women entrepreneurs to increase income.